Modified Methacrylate Hydrogels Improve Tissue Repair after Spinal Cord Injury - Hejčl, Aleš; Růžička, Jiří; Kekulová, Kristýna; Svobodová, Barbora; Proks, Vladimír; Macková, Hana; Jiránková, Kateřina; Kárová, Kristýna; Machová Urdziková, Lucia; Kubinová, Šárka; Cihlář, Jiří; Horák, Daniel; et al. (International journal of molecular sciences, 2018)
Methacrylate hydrogels have been extensively used as bridging scaffolds in experimental spinal cord injury (SCI) research. As synthetic materials, they can be modified, which leads to improved bridging of the lesion. Fibronectin, a glycoprotein of the extracellular matrix produced by reactive astrocytes after SCI, is known to promote cell adhesion. We implanted 3 methacrylate hydrogels: a scaffold based on hydroxypropylmethacrylamid (HPMA), 2-hydroxyethylmethacrylate (HEMA) and a HEMA hydrogel with an attached fibronectin (HEMA-Fn) in an experimental model of acute SCI in rats. The animals underwent functional evaluation once a week and the spinal cords were histologically assessed 3 months after hydrogel implantation. We found that both the HPMA and the HEMA-Fn hydrogel scaffolds lead to partial sensory improvement compared to control animals and animals treated with plain HEMA scaffold. The HPMA scaffold showed an increased connective tissue infiltration compared to plain HEMA hydrogels. There was a tendency towards connective tissue infiltration and higher blood vessel ingrowth in the HEMA-Fn scaffold. HPMA hydrogels showed a significantly increased axonal ingrowth compared to HEMA-Fn and plain HEMA; while there were some neurofilaments in the peripheral as well as the central region of the HEMA-Fn scaffold, no neurofilaments were found in plain HEMA hydrogels. In conclusion, HPMA hydrogel as well as the HEMA-Fn scaffold showed better bridging qualities compared to the plain HEMA hydrogel, which resulted in very limited partial sensory improvement.
Keywords: hematoencefalická bariéra; Biomarkers; Axons; spinal cord injury; Methacrylates; plantar test; Spinal Cord Injuries; Blood-Brain Barrier; regenerace nervu; Animals; extracelulární matrix; axony; biokompatibilní materiály; Wound Healing; Extracellular Matrix; exprese genu; Biocompatible Materials; Nerve Regeneration; locomotor test; biologické markery; Neovascularization, Physiologic; fyziologická neovaskularizace; methakryláty; krysa rodu Rattus; hojení ran; Disease Models, Animal; Connective Tissue; modely nemocí na zvířatech; Rats; tkáňové podpůrné struktury; zvířata; pojivová tkáň; Gene Expression; hydrogely; Hydrogels; connective tissue; hydrogel; poranění míchy; Tissue Scaffolds; neurofilaments